Implementasi Undang-Undang Nomor 18 Tahun 2019 Tentang Pesantren Terhadap Pengelolaan Pondok Pesantren - Panut Panut; Giyoto Giyoto; Yusuf Rohmadi (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to describe the implementation of Law Number 18 of 2019 concerning Islamic Boarding Schools on the management of pesantren in Kebumen Regency in 2020-2021; describe the problems of education management, availability of infrastructure and financing in Islamic boarding schools; and describe strategies for solving problems of education management, availability of infrastructure and financing in Islamic boarding schools in terms of Law Number 18 of 2019 in Kebumen Regency in 2020-2021. This study used descriptive qualitative method. The place of research is Islamic boarding school in Kebumen district, Central Java province. The sample criteria in this study was to use purposive sampling. The sample taken in this study was from 2 salafiyah Islamic boarding schools consisting of one advanced salafiyah cottage and one undeveloped salafiyah cottage. The participants of this research are the leaders of Islamic boarding schools. Informants in this study were students, ustadz/ustadzah, managers, and guardians of students. Data collection techniques in this study using documents, in-depth interviews, and observation. The method used to check the validity of the data is the credibility test (triangulation, discussion with colleagues, and member check), transferability test, dependability test, and confirmability test. The data analysis technique used in this research is through the field process. The stages in analyzing the data in this study are analysis before in the field, analysis while in the field (data reduction, data presentation, drawing conclusions). The results showed that: 1). implementation of Law Number 18 of 2019 concerning Islamic boarding schools for the management of Islamic boarding schools in Kebumen Regency in 2020-2021 has been carried out well, especially in advanced Salafiah Islamic Boarding Schools; 2). problems of education management, availability of infrastructure and financing in Islamic boarding schools in terms of Law Number 18 of 2019 in Kebumen Regency in 2020-2021 for salafiah Islamic boarding schools that have developed almost none, but salafiah Islamic boarding schools that have not advanced in all three aspects experiencing problems; 3). problem solving strategies, especially for salafiah Islamic boarding schools that have not developed yet, by conducting comparative studies to Islamic boarding schools that have good governance, recruiting human resources who understand information systems and technology, submitting infrastructure budgets to related parties, collaborating with Lazis and Baznas in particular. related to the completion of education financing in Islamic boarding schools, as well as developing a network of general donors and networks through alumni.